2015
DOI: 10.1111/hiv.12281
|View full text |Cite
|
Sign up to set email alerts
|

The ASSURE study: HIV‐1 suppression is maintained with bone and renal biomarker improvement 48 weeks after ritonavir discontinuation and randomized switch to abacavir/lamivudine + atazanavir

Abstract: Objectives HIV treatment guidelines endorse switching or simplification of antiretroviral therapy in therapy‐experienced patients with suppressed viraemia; ritonavir discontinuation may also enhance tolerability and reduce long‐term adverse events (AEs). This open‐label, multicentre, noninferiority study enrolled HIV‐1‐infected, treatment‐experienced adults with confirmed HIV‐1 RNA ≤ 75 HIV‐1 RNA copies/mL currently receiving tenofovir/emtricitabine + atazanavir/ritonavir (TDF/FTC + ATV/r) for ≥ 6 months with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…However, the ASSURE (A Simplification Study of Unboosted Reyataz with Epzicom) trial showed a nonsignificant improvement in eGFR after switching from TDF to abacavir (+0.8 vs . −1.3 in those who continued TDF), but significantly better evolution in tubular proteinuria . A significant improvement in eGFR, albuminuria and phosphataemia was also found in a recent study where TDF was switched to abacavir, regardless of whether or not patients continued with atazanavir .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, the ASSURE (A Simplification Study of Unboosted Reyataz with Epzicom) trial showed a nonsignificant improvement in eGFR after switching from TDF to abacavir (+0.8 vs . −1.3 in those who continued TDF), but significantly better evolution in tubular proteinuria . A significant improvement in eGFR, albuminuria and phosphataemia was also found in a recent study where TDF was switched to abacavir, regardless of whether or not patients continued with atazanavir .…”
Section: Discussionsupporting
confidence: 60%
“…In the ASSERT (KIVEXA Vs TRUVADA, Both Administered With Efavirenz, In ART-Naive Subjects) study, the use of TDF was associated with a significant increase in tubular proteinuria in comparison with the use of abacavir, but there were no differences in eGFR [19], as observed in the STEAL (Simplification with Tenofovir-Emtricitabine or Abacavir-Lamivudine) study [20]. However, the ASSURE (A Simplification Study of Unboosted Reyataz with Epzicom) trial showed a nonsignificant improvement in eGFR after switching from TDF to abacavir (+0.8 vs. À1.3 in those who continued TDF), but significantly better evolution in tubular proteinuria [21]. A significant improvement in eGFR, albuminuria and phosphataemia was also found in a recent study where TDF was switched to abacavir, regardless of whether or not patients continued with atazanavir [22].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…While the effects of the nucleotide reverse transcriptase inhibitor (NRTI) tenofovir disoproxil fumarate (TDF) on bone resorption and BMD are well established [2528*, 29, 30*], the effects of the PIs on BMD are less clear. However, most studies suggest an association between PI use and BMD loss [15, 31**35*].…”
Section: The Bone Effects Of the Hiv Protease Inhibitorsmentioning
confidence: 99%
“…Both cART-naïve and virologically suppressed HIV-infected patients exposed to TDF experience 1–3% more bone loss than those exposed to other NRTIs in [5761]. Additionally, reversible TDF-associated bone loss has been observed in healthy, HIV-uninfected men and women taking TDF for pre-exposure prophylaxis (PrEP) [6264], thus confirming the effects of TDF on bone beyond what can be attributed to viral or immune factors.…”
Section: Proposed Mechanisms Of Hiv-associated Bone Lossmentioning
confidence: 92%